Hair Fall Losing Elegancy and Personality??-Homoeopathic Hair Care (Homoeopathy for All, 2021)
Homoeopathy is considered as one of the very best alternative system for treating hair loss. Hair loss can affect scalp or entire body. It can be the result of heredity, hormonal changes, medical conditions or medications. Anyone like men, women and children can experience hair loss. Baldness typically refers to excessive hair loss from scalp. Hereditary hair loss with age is the most common cause of baldness. Some people prefer to let their baldness run its course untreated and unhidden.
Keywords: Clinical Presentation; Diagnosis; MANAGEMENT